2004
DOI: 10.1080/00288233.2004.9513621
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of effluent‐derived faecal microbes in grass buffer strips

Abstract: A series of field experiments assessed the ability of sloping (8°) 5-m-long by 2-m-wide grass buffer strips to trap the faecal microbes Escherichia coli and Campylobacter. The microbes, applied within dairy-farm effluent, were washed into the strips by surface runoff generated at rates of 4-13 litres/min using a water sprinkler system. The effluent and surface and subsurface outflows at the lower end of each plot were sampled for microbial analysis. Flow rate influenced the timing of peak microbial concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 8 publications
3
28
0
Order By: Relevance
“…At present c. 50% of the stream is fenced, but we have frequently observed stock within these fenced areas, near the stream. Dense vegetation within fenced riparian areas has the potential to reduce faecal pathogen input in surface run-off, provided the flow rates are sufficiently low (Collins et al 2004). Another positive outcome of this might be increased stream shading from riparian plants, resulting in lower water temperatures and improved DO during summer as a result of reduced photosynthetic and heterotrophic respiration (Wilcock & Nagels 2001).…”
Section: Faecal Pollutionmentioning
confidence: 99%
“…At present c. 50% of the stream is fenced, but we have frequently observed stock within these fenced areas, near the stream. Dense vegetation within fenced riparian areas has the potential to reduce faecal pathogen input in surface run-off, provided the flow rates are sufficiently low (Collins et al 2004). Another positive outcome of this might be increased stream shading from riparian plants, resulting in lower water temperatures and improved DO during summer as a result of reduced photosynthetic and heterotrophic respiration (Wilcock & Nagels 2001).…”
Section: Faecal Pollutionmentioning
confidence: 99%
“…While there is significant evidence of the direct impact of cattle on rural waterways (6,9,11,31), sheep have nevertheless been implicated as contributors to bacterial indicator and pathogen loadings in rivers and streams (8,10,18,20). It has been suggested that the total number of Escherichia coli per hectare of pasture are higher for sheep than for cattle (30).…”
mentioning
confidence: 99%
“…In a study of pig slurry flowing down a slope, it was reported that all of the bacteria were absorbed and retained by the soil under relatively dry antecedent conditions (9). In contrast, studies with saturated soils often show poor removal of bacteria (4,5). This can be attributed, in part, to a lack of infiltration, which limits interaction of runoff with the soil matrix (1,3).…”
mentioning
confidence: 99%